Electrogenic colonic ion transport in Hirschsprung's disease: reduced secretion to the neural secretagogues acetylcholine and iloprost. Issue 10 (October 1993) - Hardy, S P; Smith, P M; Bayston, R; Spitz, L
Abstract : The effects of the abnormal innervation in Hirschsprung's disease on colonic ion transport were examined in vitro using Ussing chambers. The response of the mucosal/submucosal preparations to different secretagogues were investigated in aganglionic and ganglionic rectosigmoid and transverse colon from children with Hirschsprung's disease and compared with normally innervated colon from children with anorectal anomalies. Basal values were similar in aganglionic and ganglionic rectosigmoid colon. Neurally mediated secretion with iloprost (10(-6) M) and acetylcholine (900 and 9 microM) was considerably reduced in aganglionic colon compared with normally innervated ganglionic colon. The ganglionic colon proximal to the aganglionic colon also had a reduced response to acetylcholine despite a normal acetylcholinesterase staining pattern. The responses to Escherichia coli STa enterotoxin (50 MU/ml) and isobutylmethylxanthine (10(-3) M) were similar in ganglionic and aganglionic colon. The response to STa enterotoxin was not changed by the nerve blocking agent tetrodotoxin (10(-6) M). The data show that colonocytes from aganglionic colon are capable of a normal secretory response if stimulated directly by cAMP or cGMP acting secretagogues but secretion in response to neurally mediated secretagogues is impaired. The hypertrophied acetylcholinesterase positive nerve fibres that infiltrate the aganglionic colon are likely to contribute to the reduced secretion to acetylcholine.